2015
DOI: 10.1111/1749-4877.12165
|View full text |Cite
|
Sign up to set email alerts
|

Social dominance‐related major urinary proteins and the regulatory mechanism in mice

Abstract: Major urinary proteins (MUPs) have been proven to be non-volatile male pheromones in mice. Here, we aimed to elucidate the relationship between MUPs and dominance hierarchy, and the underlying molecular mechanisms. Dominance-submission relationship was established by chronic dyadic encountering. We found that at the urinary protein level and hepatic mRNA level, the expression of major MUPs, including Mup20, was enhanced in dominant males compared with subordinate males, indicating that MUPs might signal the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 63 publications
9
37
0
Order By: Relevance
“…However, further analyses are needed to confirm protein identification, evaluate variation and consistency across all Mup loci, and over a longer time and across different conditions. MUP production is dynamically regulated with changes in age27, health2829, diet30, and social status3132, and we recently found that MUP proteins are differentially regulated when males are placed in competitive social conditions33. Thus, MUP expression profiles are phenotypically plastic, rather than constitutive (developmentally fixed), and studies are needed to investigate how variation and consistency in MUP expression influences individual odor , especially under more natural conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, further analyses are needed to confirm protein identification, evaluate variation and consistency across all Mup loci, and over a longer time and across different conditions. MUP production is dynamically regulated with changes in age27, health2829, diet30, and social status3132, and we recently found that MUP proteins are differentially regulated when males are placed in competitive social conditions33. Thus, MUP expression profiles are phenotypically plastic, rather than constitutive (developmentally fixed), and studies are needed to investigate how variation and consistency in MUP expression influences individual odor , especially under more natural conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to subordinate animals, dominant males have higher levels of major urinary proteins (MUPs) that bind to signalling volatile compounds (e.g. 2-secbutyl-4,5-dihydrothiazole and 3,4-dehydro-exo-brevicomin) (Apps, Rasa, & Viljoen, 1988;Guo, Fang, Huo, Zhang, & Zhang, 2015;Harvey, Jemiolo, & Novotny, 1989;Humphries, Robertson, Beynon, & Hurst, 1999;Kaur et al, 2014;Nelson et al, 2015;Stowers & Kuo, 2015). Some of these urinary proteins (e.g.…”
Section: Individuals Behave Consistently and Appropriately According mentioning
confidence: 99%
“…Social interactions in the laboratory have been found to affect the regulation of urinary MUPs. 8,11 However, studies are needed to determine whether MUP production is socially regulated in more natural conditions (ecological validation). There are increasing studies showing changes in gene expression due to individual versus group housing.…”
Section: Introductionmentioning
confidence: 99%